2022
DOI: 10.1155/2022/9162584
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Characteristics, Experience, and Enlightenment of Leisure and Sports Policy and Public Health Development in Developed Countries

Abstract: Public health highlights “public utilities,” emphasizes the attributes of public goods and services, and aims to clarify the responsibility of government leadership; highlighting “maintaining health equity” aims to make it clear that public health not only guarantees health but also focuses on fairness; the purpose extends to “maintaining social stability and development,” emphasizing that the function of public health is not only to protect health; emphasizing that public health is “one science” and aims to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In peripheral cities, given the relative backwardness of the soft environment such as the institutional environment and policy preferences, the development of DE may accelerate the flow of all kinds of factors from the peripheral cities to the central city, thus generating the "siphon effect" phenomenon, leading to the "Matthew effect" (i.e., "the weaker is weaker, the stronger is stronger"), further distorting the allocation of factors, and impeding the enhancement of the performance of urban EWP (Cui et al, 2023). However, with the rising level of DE development in cities, DE development can effectively reduce the cost of searching, trading, matching, and copying by alleviating information asymmetry (Xue and Li, 2022), thus reducing the transaction barriers, breaking the market boundary, and expanding the scope of the market, which is conducive to the flow of factors in a larger space, and optimizing the distortion of factor allocation (Qu et al, 2023). Moreover, the DE can replace and eliminate the traditional backward industries with high pollution and high energy consumption through the substitution effect, and it can apply new technologies to empower and improve the efficiency of traditional industries through the empowerment effect, thus giving rise to new industries, new business forms, and new modes, opening up new channels for factor flows, enhancing the efficiency of factor allocation, and thus improving the performance of urban EWP (Bao et al, 2023).…”
Section: Factor Allocation Optimization Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In peripheral cities, given the relative backwardness of the soft environment such as the institutional environment and policy preferences, the development of DE may accelerate the flow of all kinds of factors from the peripheral cities to the central city, thus generating the "siphon effect" phenomenon, leading to the "Matthew effect" (i.e., "the weaker is weaker, the stronger is stronger"), further distorting the allocation of factors, and impeding the enhancement of the performance of urban EWP (Cui et al, 2023). However, with the rising level of DE development in cities, DE development can effectively reduce the cost of searching, trading, matching, and copying by alleviating information asymmetry (Xue and Li, 2022), thus reducing the transaction barriers, breaking the market boundary, and expanding the scope of the market, which is conducive to the flow of factors in a larger space, and optimizing the distortion of factor allocation (Qu et al, 2023). Moreover, the DE can replace and eliminate the traditional backward industries with high pollution and high energy consumption through the substitution effect, and it can apply new technologies to empower and improve the efficiency of traditional industries through the empowerment effect, thus giving rise to new industries, new business forms, and new modes, opening up new channels for factor flows, enhancing the efficiency of factor allocation, and thus improving the performance of urban EWP (Bao et al, 2023).…”
Section: Factor Allocation Optimization Effectsmentioning
confidence: 99%
“…Urban EWP (EPW): The current common methods for EWP measurement are as follows: (1) the ratio method, such as using the ratio of social welfare or happy life index to the ecological footprint; Wang and Li 10.3389/fevo.2024.1361741 Frontiers in Ecology and Evolution frontiersin.org and (2) the non-parametric method, such as data envelopment analysis. Since it is difficult for a single indicator to measure both factors at the same time, and the evaluation system constructed through tends to duplicate information (Cui et al, 2023), with reference to Tang and Zhao (2023) and Xue and Li (2022), in this paper, the Super SBM-DEA method is used to measure urban EWP using efficiency values of inputs and outputs. EWP refers to the efficiency of natural ecological factor inputs into human welfare, in which natural ecological factor inputs reflect the consumption of natural resources and EE disturbance by human activities.…”
Section: Explained Variables: Urban Ewpmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%